Predicting mobile banking adoption: An integration of TAM and TBP with trust and perceived risk - Ziad Aldammagh; Rabah Abdeljawad; Tareq Obaid (Financial Internet Quarterly, 2021)
Mobile banking has been a game changer for financial organizations in terms of remote banking services. However, many customers remain uncertain due to its security. Therefore, improving the comprehension of the customer's reasons and methods of using bank sites, including their behaviour towards e-banking, is crucial. This article discusses the matter by suggesting a technology acceptance model that integrates the theory of the planned behavior model in the classic TAM model with trust and perceived risk in order to elucidate the aspects that influence users' acceptance of mobile banking applications in Palestine. This study is designed to give both theoretical and empirical support for e-commerce adoption. We are also capable in providing particular marketing ideas for practitioners in relation to the uptake of mobile banking.
Keywords: O1; O16; 330; TAM; TPB mobile banking; perceived risk; trust; Palestine